2017
DOI: 10.1007/s10800-016-1035-0
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-doped mesoporous carbon nanofibres as free-standing cathodes for lithium–oxygen batteries

Abstract: of Co nanoparticles enhances the degree of graphitization of the CNFs, which is beneficial to CNF conductivity. Measured BET surface areas of Co-doped CNFs are in the range of 40-300 m 2 g − 1 , depending on Co content. Results show that the Li-O 2 cell comprising the Co-doped CNF free-standing cathodes can deliver specific capacities of 3700 mA h g − 1 based on the total mass of the electrodes and good cycling performance is achieved at the curtailed capacity of 100 mA h g − 1 . The good performance of the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Co and CoO particles in the Co-CoO/N-CNR material acted as nucleation sites for Li2O2, delaying the onset of complete surface coverage during discharge. This result has been replicated in other work investigating Co doped carbon fibers as air cathode materials, and is significant as the ability to continuously form and decompose Li2O2 improves rate capability and cycle stability [222]. Li2O2 has a higher energy of adsorption onto Co and CoO than carbon, limiting the formation of Li2CO3 in the doped fibres, which serves to improve cycling performance and limit parasitic side reactions.…”
Section: Electrochemically Active Electrospun Fibres: Li-airsupporting
confidence: 59%
“…Co and CoO particles in the Co-CoO/N-CNR material acted as nucleation sites for Li2O2, delaying the onset of complete surface coverage during discharge. This result has been replicated in other work investigating Co doped carbon fibers as air cathode materials, and is significant as the ability to continuously form and decompose Li2O2 improves rate capability and cycle stability [222]. Li2O2 has a higher energy of adsorption onto Co and CoO than carbon, limiting the formation of Li2CO3 in the doped fibres, which serves to improve cycling performance and limit parasitic side reactions.…”
Section: Electrochemically Active Electrospun Fibres: Li-airsupporting
confidence: 59%
“…Crespiera et al. fabricated a mesoporous carbon nanofiber with cobalt nanoparticles as free‐standing cathodes in lithium‐oxygen batteries [192] . After a complete discharge process is finished, it can be found that the presence of Co nanoparticles affected the morphology of discharge products (Figure 9a).…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…a) Co nanoparticles affected the morphology of discharge products on mesoporous carbon nanofibers. Reproduced with permission [192] . Copyright 2017, Springer.…”
Section: Lithium Batteriesmentioning
confidence: 99%
“…N‐doped vertically aligned CNTs and graphene show improved electrocatalytic activity and stability for the ORR reactions in alkaline media. Therefore, heteroatom doping has been adopted to manipulate the local electronic structures of cathode catalysts, such as graphene, carbon nanotubes, mesoporous carbon, perovskites, and metal oxides for Li–O 2 batteries.…”
Section: Heteroatom Dopingmentioning
confidence: 99%